2020
DOI: 10.1158/1078-0432.ccr-19-1513
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Prospective, Randomized, Multicenter, Open-Label Study of GX-188E, an HPV DNA Vaccine, in Patients with Cervical Intraepithelial Neoplasia 3

Abstract: Purpose: To determine the efficacy of the therapeutic DNA vaccine GX-188E for inducing regression of cervical intraepithelial neoplasia (CIN) 3. Patients and Methods: We conducted a prospective, randomized, multicenter, open-label, phase II clinical trial of GX-188E in CIN3 patients positive for human papillomavirus (HPV) type 16/ 18. The primary endpoint was to determine the histopathologic regression to CIN1 at visit seven (V7; 20 weeks after the first GX-188E injection), and an extension study was pursued u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…BVAC-C consists of B cells and monocytes utilized as APCs, loaded with HPV16/18 E6/E7 peptides, and transfused back into patients with recurring or metastatic cervical cancer (NCT02866006). Data from the Phase I trial 108 showed that BVAC injection resulted in mild AEs, and no DLTs in patients with platinum-resistant recurrent cervical cancer. The overall response rate was 11%, and the median progression-free survival was 6.8 months.…”
Section: Cell-based Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…BVAC-C consists of B cells and monocytes utilized as APCs, loaded with HPV16/18 E6/E7 peptides, and transfused back into patients with recurring or metastatic cervical cancer (NCT02866006). Data from the Phase I trial 108 showed that BVAC injection resulted in mild AEs, and no DLTs in patients with platinum-resistant recurrent cervical cancer. The overall response rate was 11%, and the median progression-free survival was 6.8 months.…”
Section: Cell-based Vaccinesmentioning
confidence: 99%
“…Patients also exhibited increased activation of natural killer T (NKT) cells, NK cells, and HPV-specific T cells post-vaccination. 108…”
Section: Cell-based Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flt3L and tpa are included in the fusion gene to promote antigen presentation and trafficking of the fused protein to the secretory pathway, respectively [ 54 ]. Recently, GX-188E was described to be highly efficacious in patients with grade 3 cervical intraepithelial neoplasia (CIN3) (NCT02139267) [ 55 ].…”
Section: Hpv Vaccinesmentioning
confidence: 99%
“…Since it was first reported that immunization of naked plasmid DNA encoding foreign protein induces an Ag-specific immune response in mammals in the early 1990s ( 164 ), DNA vaccines have been widely tested in various pathogen models. Although DNA vaccines have not been approved for humans to date, their immunogenicity and therapeutic effects have long been tested across various clinical trials for infectious diseases as well as human papillomavirus-mediated cervical intraepithelial neoplasia ( 165 166 ). DNA vaccines expressing full-length or truncated forms of SARS-CoV S protein induced humoral and cellular immunity, supplying protection against SARS-CoV infection in murine models ( 98 124 125 ).…”
Section: Vaccine Researchmentioning
confidence: 99%